Investigation and Exploration of the Current Situation and Feasible Paths of Agricultural Waste Resource Utilization Development under the "Dual Carbon" Strategy: Taking Wuhe, Anhui as an Example - Wu, Xiandou; Kong, Ying; Zhou, Zejiong (International Journal of Social Sciences and Public Administration, 2024)
With the continuous development of rural social economy in China, the quality of life and agricultural production level of farmers have significantly improved. The lifestyle of farmers has changed significantly, and some traditional agricultural production links have been broken, resulting in a sharp increase in the quantity and variety of agricultural waste. The resource utilization of agricultural waste can not only improve the efficiency of rural resource utilization, but also reduce agricultural waste pollution and protect the rural environment. This article takes the agricultural waste resource utilization in Wuhe County, Anhui Province as an example for investigation and analysis. The main conclusions are as follows: the significance of agricultural waste resource utilization is significant, and resource utilization treatment is very necessary; Agricultural waste has a wide range of sources, and strengthening classification and integration is particularly important; Group cognition needs to be improved, and guiding education is imperative; The subjective willingness of villagers is good, and policy implementation is expected to be popularized; The four types of factors have a significant impact, and targeted measures are taken. Based on the results of the practical investigation, this article mainly proposes the following feasible path suggestions for agricultural waste resource utilization: publicity and education, improving the awareness of villagers; Government guidance and increased regulatory support; Facing market pain points and enhancing industrial vitality; Strengthen classification integration and promote technological innovation; Strengthen scientific layout and promote benefit sharing.